The Bumba-Meu-Boi Rei da Boiada Festival : reflections on a cultural tourist attraction of the city of Parnaíba – Piauí. - Nascimento Neto, Otavio Altino do (2022)
The Bumba-meu-boi is a traditional festival that takes place in the Northeast of Brazil, and is one of the most important festivals in Brazilian popular culture. In Parnaíba, in the state of Piauí, there is Rei da Boiada cultural group that carries high symbolic value for those who take part in the ritual. This group is part of the cultural heritage of the city that is home to the participants, who invest a great deal of love, dedication and effort to the art, dance and local culture. Based on a case study of the Rei da Boiada Group, this qualitative research study investigates whether the Bumba-meu-boi Rei da Boiada cultural festival can be considered a tourist attraction. The methods used in this research included a bibliographic review, field study and interviews. Data were gathered through semi-structured interviews and field observations from 2015 to 2019. The descriptive and explanatory method was used for the data analysis. It was concluded that the group is culturally rich and can be considered a tourist attraction, as it is part of the “Festa de Juninha” – the June festival that attracts tourists. But there has been little research on the Bumba-meu-boi itself, despite its great potential to contribute to the development of cultural tourism in the city.